Causes and Effects of Trauma in Bhutanese Nepali Diasporic Poetry - Timalsina, Ramji (Molung Educational Frontier, 2020)
This study aims to explore the causes and effects of trauma in Bhutanese Nepali diasporic poetry. It discusses the connection between the individual and collective trauma. Bhutanese Nepali diasporic poetry gives expression to centuries-long marginalization and sufferings of this community. The series of suffering started from the time the people of Nepali origin reached Bhutan for permanent settlement. It continued with their expulsion, life as refugees and finally in the resettled life in the West. Their experiences of suffering caused trauma on both the personal and collective levels. To explore how it is represented in their poetic creations, I have done this study with the use of constructivist trauma theory in the analysis of the six purposively selected poems that deal with causes and effects of trauma. Constructivist trauma theory deals with trauma as a social construct. The experiences of the people are traumatic, and the discourses on trauma make the individual and social trauma acute and understandable. The study has found that the history of sufferings and the consequent experiences are the causes of their trauma. As a result of trauma, their mentality has been badly affected. The speakers in the poems and the community at the level of representation have been fearful, purposeless and disoriented. The victims’ vulnerable existential condition has been reflected in their alternative mode of living on, disability, helplessness and aloneness that has caused significant bearing on the construction of their identity. Their psychology has been filled with troubling past and unstable present mentality resulting into the feeling of being demeaned and diminished. At the same time, these poems have depicted the combination of personal and collective trauma. I believe that this study paves way to further studies on Bhutanese Nepali diasporic literature from the perspective of trauma theory.